HUBUNGAN KEKURANGAN ENERGI KRONIK (KEK) DENGAN STUNTING DI WILAYAH PUSKESMAS MOJOTENGAH - Indrawati aristya rini; Romdiyah; Dewi Candra Resmi; Ari setyawati (Fakultas Ilmu Kesehatan, 2025)
Background: Stunting is a condition that occurs in toddlers who experience growth failure due to chronic malnutrition during the First 1000 Days of Life (HPK). This can be influenced by maternal factors with a state of Chronic Energy Deficiency (KEK). According to WHO (2016), an estimated 156 million children worldwide suffered from stunting in 2015 or 23% of all children worldwide. Objective: to determine the relationship between KEK and the incidence of Stunting in the Mojotengah Health Center area. Method: this study used a retrospective method with a CrossSectional approach. The study population was stunted toddlers aged 1-4 years in 2022 at the Mojotengah Health Center as many as 367 toddlers. The sampling technique used the Simple Random sampling technique obtained 148 toddler respondents. The measuring instrument used was the documentation sheet from the health center. Data analysis used frequency distribution and the Chi Square test. Research results: Based on the results of the study, it shows that pregnant women with KEK with the incidence of very short child stunting of 66.2% compared to pregnant women with KEK experiencing short child stunting of 33.8%. The conclusion is that there is a relationship between KEK and the incidence of Stunting in children with a p value = 0.013 <0.005. It is recommended that further research can add other factors such as nutrition in pregnant women.